Political Economy of Health Workforce Policy : The Chhattisgarh Experience with a Three-year Course for Rural Health Care Practitioners - Raha, Shomikho; Bossert, Thomas; Vujicic, Marko (World Bank, Washington, DC, 2013)
This case study analyzes the reasons for adoption and the implementation process of a key policy in Chhattisgarh state, India, to create a rural cadre of trained physicians in order to address the acute shortage of doctors in the state's primary health facilities. It documents the experience specific to Chhattisgarh state, but with its attention to the policy processes and implementation challenges associated, it also highlights the necessity of a political economy perspective currently missing in much of the published literature on human resources for health. A principal lesson of this case concerns why it matters how interests of various stakeholders who had interests in the three-year course are included early in the policy process, namely the anticipated opposition of the medical doctor community represented by the Indian Medical Association (IMA) and the interests of the students themselves and their desire to be given appropriate status as medical doctors. This case study addresses the legal hurdles faced and the importance of institutional support structures to maintain quality standards and provide for grievance procedures. Through this case study, it also becomes apparent why the role of institutional ownership of policy matters rather than success or failure of policy that is linked entirely to the authority of a few key appointed officials.